Clinical and molecular response to alpha1-oleate treatment in patients with bladder cancer - Haq, Farhan; Sabari, Samudra; Háček, Jaromir; Brisuda, Antonín; Ambite, Ines; Cavalera, Michele; Esmaeili, Parisa; Wan, Murphy Lam Yim; Ahmadi, Shahram; Babjuk, Marek; Svanborg, Catharina (Cancer medicine, 2024)
BACKGROUND: The tumoricidal complex alpha1-oleate targets bladder cancer cells, triggering rapid, apoptosis-like tumor cell death. Clinical effects of alpha1-oleate were recently observed in patients with non-muscle invasive bladder cancer (NMIBC), using a randomized, placebo-controlled study protocol. AIMS: To investigate if there are dose-dependent effects of alpha1-oleate. MATERIALS AND METHODS: Here, patients with NMIBC were treated by intravesical instillation of increasing concentrations of alpha1-oleate (1.7, 8.5, or 17 mM) and the treatment response was defined relative to a placebo group. RESULTS: Strong, dose-dependent anti-tumor effects were detected in alpha1-oleate treated patients for a combination of molecular and clinical indicators; a complete or partial response was detected in 88% of tumors treated with 8.5 mM compared to 47% of tumors treated with 1.7 mM of alpha1-oleate. Uptake of alpha1-oleate by the tumor triggered rapid shedding of tumor cells into the urine and cell death by an apoptosis-like mechanism. RNA sequencing of tissue biopsies confirmed the activation of apoptotic cell death and strong inhibition of cancer gene networks, including bladder cancer related genes. Drug-related side effects were not recorded, except for local irritation at the site of instillation. DISCUSSION AND CONCLUSIONS: These dose-dependent anti-tumor effects of alpha1-oleate are promising and support the potential of alpha1-oleate treatment in patients with NMIBC.
Keywords: apoptóza; vztah mezi dávkou a účinkem léčiva; cellular uptake; Female; výsledek terapie; ženské pohlaví; Apoptosis; Oleic Acid; lidé; aplikace intravezikální; cell shedding; kyselina olejová; Antineoplastic Agents; protinádorové látky; Treatment Outcome; Aged, 80 and over; Dose-Response Relationship, Drug; Male; Urinary Bladder Neoplasms; Aged; Administration, Intravesical; nádory močového měchýře; lidé středního věku; senioři nad 80 let; alpha1‐oleate complex; senioři; mužské pohlaví; Middle Aged; non‐muscle invasive bladder cancer; gene expression; Humans